Preparation method of high-conductivity high-porosity carbon paper for proton exchange membrane fuel cell
Patent Information
- Application Number
- CN202311100912.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-30
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2043-08-30
AI Technical Summary
多孔导电碳纸因具有良好的导电性和较好的孔隙度,常被运用在气体扩散层中,现有的碳纸在制备时会以酚醛树脂为基质炭的前驱体,采用浸渍成型和热处理等工艺来制造,但在碳纸在浸渍过程中,酚醛树脂与碳纸原纸的相容性较差,阻碍了界面结合的形成,减弱酚醛树脂纤维的粘附力,在热处理后,碳纸产品的强度和导电性因界面结构较弱而降低
[0017]与现有技术相比,本发明利用丙烯酸甲酯单体接枝CNF来增大接触角,改善CNF的疏水性,使得CNF均匀分散在在酚醛树脂溶液中;通过在混合溶液中加入一定量的CNF接枝丙烯酸甲酯,提高碳纸在热压阶段的浸渍量,减少浸渍液的流失并且能更充分进行固化交联,使酚醛树脂能够更多的留在碳纸原纸上,之后对碳纸原纸进行碳化处理,由于在混合溶液中加入一定量的CNF接枝丙烯酸甲酯,增加增强了碳纸的界面结合,从而改善了基质炭与碳纤维之间的载流子输运,提供更多的电子传输途径,降低碳纸的电阻率,从而提升碳纸的导电性,其次,碳纸中基质炭呈网状均匀分布,增大孔隙,促进孔隙连通率的增加和低残炭率,为气体的扩散提供了更多的通道,实现气体渗透率的增加。
Smart Images

Figure CN116979080B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of carbon paper preparation technology, and specifically to a method for preparing high-conductivity, high-porosity carbon paper for proton exchange membrane fuel cells. Background Technology
[0002] A proton exchange membrane fuel cell (PEMFC) consists of a membrane electrode assembly, a gas diffusion layer, gaskets, and bipolar plates. The gas diffusion layer is a crucial component of the PEMFC, influencing the performance of the fuel cell. Porous conductive carbon paper, due to its good conductivity and porosity, is often used in the gas diffusion layer. Current carbon paper production processes use phenolic resin as a precursor for the matrix carbon, employing impregnation molding and heat treatment. However, during impregnation, the poor compatibility between the phenolic resin and the carbon paper hinders interfacial bonding, weakening the adhesion of the phenolic resin fibers. After heat treatment, the strength and conductivity of the carbon paper product decrease due to the weak interfacial structure. To improve the performance of carbon paper, current methods employ double-layer molding technology and lamination structure to improve the pore size distribution of carbon felt, different heat treatment temperatures and material amounts, introducing carbon nanotubes, pitch-based carbon, coke or polytetrafluoroethylene coatings onto carbon fibers, and adding graphite powder or carbon black to the impregnating agent. These methods aim to improve the conductivity and high porosity of carbon paper, but the improvement effect is not significant, and the performance of carbon paper cannot be significantly enhanced. Summary of the Invention
[0003] The purpose of this invention is to provide a method for preparing highly conductive and highly porous carbon paper for proton exchange membrane fuel cells. The carbon paper prepared by this invention has the advantages of high conductivity, uniform pore size distribution, and low impedance, effectively improving fuel cell performance.
[0004] The technical solution provided by this invention is as follows: A method for preparing high-conductivity, high-porosity carbon paper for proton exchange membrane fuel cells, comprising the following steps:
[0005] S1. CNF is grafted onto methyl acrylate monomer to obtain CNF-grafted methyl acrylate.
[0006] S2. Prepare a mixed solution of phenolic resin and ethanol solution, add CNF-grafted methyl acrylate to the mixed solution, and stir ultrasonically to obtain an adhesive; then impregnate the carbon paper base paper in it and perform ultrasonic treatment, remove the carbon paper base paper and lay it flat to obtain a preform;
[0007] S3. The preform is dried in an oven to obtain dried carbon paper, which is then compressed and molded by hot pressing in a vulcanizing bed to obtain hot-pressed carbon paper base paper.
[0008] S4. The hot-pressed carbon paper base paper is carbonized in a high-temperature tube furnace, and finally cooled to obtain carbonized carbon paper.
[0009] In the above-mentioned method for preparing high-conductivity, high-porosity carbon paper for proton exchange membrane fuel cells, in step S1, the process of grafting CNF with methyl acrylate monomer involves taking 5-15 parts of CNF by dry weight, diluting it with deionized water to a mass concentration of 1-5%, and placing it in a constant temperature water bath at 25-35℃. The pH of the CNF suspension is adjusted to 0.8-1.5 with nitric acid. Next, cerium ammonium nitrate is added to the suspension at a concentration of 5.0 mmol / L. After stirring evenly at a speed of 400-600 rpm, nitrogen gas is introduced for 30 minutes to remove oxygen from the reaction system. Finally, methyl acrylate monomer is added dropwise using a peristaltic pump for graft polymerization. The reaction is terminated after 1.5-2.5 hours. After the reaction is completed, the solid is separated by centrifugation at a speed of 8000-12000 rpm and a temperature of 3-5℃ for 10-20 minutes. The obtained solid is CNF-grafted methyl acrylate.
[0010] In the aforementioned method for preparing high-conductivity, high-porosity carbon paper for proton exchange membrane fuel cells, in step S1, the process of grafting CNF onto methyl acrylate monomer involves taking 10 portions of CNF by dry weight, diluting them with deionized water to a mass concentration of 2%, and placing them in a 30°C constant temperature water bath. The pH of the CNF suspension is adjusted to 1.0 using nitric acid. Next, cerium ammonium nitrate is added to the suspension at a concentration of 5.0 mmol / L. After stirring evenly at 500 rpm, nitrogen gas is introduced for 30 minutes to remove oxygen from the reaction system. Finally, methyl acrylate monomer is added dropwise using a peristaltic pump for graft polymerization. The reaction is terminated after 2 hours. After the reaction is complete, the solid is separated by centrifugation at 10,000 rpm and 4°C for 15 minutes. The obtained solid is CNF-grafted methyl acrylate.
[0011] In the aforementioned method for preparing high-conductivity, high-porosity carbon paper for proton exchange membrane fuel cells, after solid-liquid separation, the solid is first washed with deionized water until neutral to remove initiator and acid. The washed solid is then subjected to Soxhlet extraction for 24 hours using a mixture of acetone and tetrahydrofuran at a ratio of 1:2 to remove homopolymer.
[0012] In the aforementioned method for preparing high-conductivity, high-porosity carbon paper for proton exchange membrane fuel cells, in step 2, ethanol solution is used as a solvent, phenolic resin is added, and a mixed solution with a phenolic resin concentration of 12 wt% is prepared. CNF-grafted methyl acrylate is added to obtain a mixed solution with a CNF-grafted methyl acrylate mass concentration of 0.2-1.8%. The mixed solution is then ultrasonically stirred for 8-15 minutes to ensure uniform dispersion in the mixed solution and stored as a binder. The carbon paper base paper is then impregnated in the mixture and ultrasonically treated for 15-25 minutes. After removal, it is spread flat with a glass rod to ensure uniform resin penetration and is used as a preform.
[0013] In the aforementioned method for preparing high-conductivity, high-porosity carbon paper for proton exchange membrane fuel cells, the mass concentration of CNF-grafted methyl acrylate in the mixed solution is 1.6%; the ultrasonic stirring time is 10 min; and the ultrasonic treatment time is 20 min.
[0014] In the aforementioned method for preparing high-conductivity, high-porosity carbon paper for proton exchange membrane fuel cells, in step S3, the drying time in the oven is one hour and the temperature is 80°C; the sulfurized bed is hot-pressed in air at a temperature of 150°C and a pressure of 4 MPa for 1 hour.
[0015] In the aforementioned method for preparing high-conductivity, high-porosity carbon paper for proton exchange membrane fuel cells, in step S4, the hot-pressed carbon paper is carbonized in a high-temperature tube furnace with a heating rate of 8-12℃ / min, a sintering temperature of 1000-1200℃, a holding time of 1 hour, and carbonized carbon paper is obtained after cooling.
[0016] In the aforementioned method for preparing high-conductivity, high-porosity carbon paper for proton exchange membrane fuel cells, the heating rate during carbonization is 10°C / min, the sintering temperature is 1100°C, and the holding time is 1 hour.
[0017] Compared with existing technologies, this invention utilizes methyl acrylate monomer grafted with CNF to increase the contact angle and improve the hydrophobicity of CNF, allowing CNF to be uniformly dispersed in the phenolic resin solution. By adding a certain amount of CNF-grafted methyl acrylate to the mixed solution, the impregnation amount of carbon paper during the hot pressing stage is increased, the loss of impregnation solution is reduced, and more complete curing and cross-linking are achieved, allowing more phenolic resin to remain on the carbon paper base. Subsequently, the carbon paper base is carbonized. Due to the addition of a certain amount of CNF-grafted methyl acrylate to the mixed solution, the interfacial bonding of the carbon paper is enhanced, thereby improving the carrier transport between the matrix carbon and the carbon fibers, providing more electron transport pathways, reducing the resistivity of the carbon paper, and thus improving the conductivity of the carbon paper. Secondly, the matrix carbon in the carbon paper is uniformly distributed in a network, increasing the porosity, promoting the increase of pore connectivity and low carbon residue, providing more channels for gas diffusion, and achieving an increase in gas permeability. Attached Figure Description
[0018] Figure 1 A schematic diagram illustrating the mechanism of CNF grafting MMA reaction;
[0019] Figure 2 Visual representations of PF, CNF / PF, and CNFM-PF solutions;
[0020] Figure 3 A schematic diagram of water contact in CNF;
[0021] Figure 4 This is a schematic diagram of the water contact angle of CNFM;
[0022] Figure 5 The graphs of CNF and CNFM under Fourier transform infrared spectroscopy are shown.
[0023] Figure 6 For CNF and CNFM, see TG and DTG graphs;
[0024] Figure 7 SEM images of CNFM-PF / HPCP at different scales;
[0025] Figure 8 Bar charts showing the air permeability of CNFM-PF / HPCP at different ratios;
[0026] Figure 9 Tensile strength diagrams for CNFM-PF / HPCP with different ratios;
[0027] Figure 10 Resistivity histograms for CNFM-PF / HPCP at different ratios;
[0028] Figure 11 A schematic diagram showing the changes in TG and DTG for different ratios of CNFM-PF / CP;
[0029] Figure 12 Microscopic morphology images of CNFM-PF / CP with different ratios;
[0030] Figure 13 A bar chart showing the quality of carbon paper at each stage;
[0031] Figure 14 A graph showing the variation in bulk density and thickness of CNFM carbon paper with different proportions;
[0032] Figure 15 (a) is a 3D CT image of CP;
[0033] Figure 15 (b) is a 3D CT image of CNFM-PF / CP-1.6;
[0034] Figure 15 (c) shows the matrix distribution of CP;
[0035] Figure 15 (d) shows the matrix distribution of CNFM-PF / CP-1.6;
[0036] Figure 16 A histogram showing the pore size distribution of CNFM-PF / CP at different ratios;
[0037] Figure 17 Bar charts showing air permeability and porosity for different CNFM-PF / CP ratios;
[0038] Figure 18 (a) XRD patterns of CNFM-PF / CP at different ratios;
[0039] Figure 18 (b) XPS spectra of CP and CNFM-PF / CP-1.6;
[0040] Figure 18 (c) and (e) are schematic diagrams showing the changes in CP and CNFM-PF / CP-1.6C1s;
[0041] Figure 18 (d) and (f) are schematic diagrams of the high-resolution spectra of the O1s XPS peak;
[0042] Figure 18 (g) is a resistivity histogram for CNFM-PF / CP with different ratios;
[0043] Figure 18 (h) is a bar chart of the bending strength of CNFM-PF / CP with different ratios;
[0044] Figure 18(i) is a schematic diagram showing the changes in tensile strength at different ratios of CNFM-PF / CP;
[0045] Figure 19 The current density and corresponding output power density plots generated by the polarization curves of CNFM-PF / CP with different ratios;
[0046] Figure 20 A schematic diagram showing the electrochemical impedance changes of fuel cells with different ratios of CNFM-PF / CP. Detailed Implementation
[0047] The present invention will be further described below with reference to the embodiments and accompanying drawings, but this should not be construed as limiting the present invention.
[0048] Example 1: A method for preparing highly conductive and highly porous carbon paper for proton exchange membrane fuel cells, comprising the following steps:
[0049] S1. CNF is grafted onto methyl acrylate monomer to obtain CNF-grafted methyl acrylate. In this step, the process of grafting CNF onto methyl acrylate monomer involves taking 10 portions of CNF (carbon nanocellulose) by dry weight, diluting them with deionized water to a mass concentration of 2%, and adding them to a three-necked flask equipped with a stirrer. The three-necked flask is placed in a 30°C constant temperature water bath, and the pH of the CNF suspension is adjusted to 1.0 with 20% nitric acid. Next, cerium ammonium nitrate is added to the suspension at a concentration of 5.0 mmol / L (relative to the total system volume), and then the mixture is stirred at 500 rpm. After stirring evenly under the conditions, nitrogen gas was introduced for 30 minutes to remove oxygen from the reaction system. Finally, methyl acrylate monomer was added dropwise using a peristaltic pump for graft polymerization. The reaction was terminated after 2 hours. After the reaction was completed, the solid and liquid were separated by centrifugation at 10,000 rpm and 4°C for 15 minutes. After solid-liquid separation, the solid was first washed with deionized water until neutral to remove the initiator and acid. The washed solid was subjected to Soxhlet extraction for 24 hours using a mixture of acetone and tetrahydrofuran at a ratio of 1:2 to remove the homopolymer. The obtained solid was CNF-grafted methyl acrylate.
[0050] S2. Prepare a mixed solution of phenolic resin and ethanol solution. Add CNF-grafted methyl acrylate to the mixed solution and stir ultrasonically to obtain an adhesive. Then, impregnate carbon paper with the solution and sonicate it. After removing the carbon paper, lay it flat to obtain a preform. In this step, ethanol solution is used as a solvent. After adding phenolic resin, a mixed solution with a phenolic resin concentration of 12 wt% is prepared. CNF-grafted methyl acrylate is added to obtain a mixed solution with a CNF-grafted methyl acrylate mass concentration of 0.4%. Then, the mixed solution is sonicated for 10 min to ensure uniform dispersion in the mixed solution. This solution is stored as an adhesive. Then, carbon paper is impregnated with the solution and sonicated for 20 min. After removing the paper, it is laid flat with a glass rod to ensure uniform resin penetration. This solution is used as a preform.
[0051] S3. The preform is dried in an oven to obtain dried carbon paper, and then compressed and formed by hot pressing in a vulcanizing bed to obtain hot-pressed carbon paper base paper (HPCP); in this step, the drying time in the oven is one hour and the temperature is 80°C; the vulcanizing bed is hot-pressed in air at a temperature of 150°C and a pressure of 4MPa for 1 hour.
[0052] S4. The hot-pressed carbon paper base paper is carbonized in a high-temperature tube furnace, and finally cooled to obtain carbonized carbon paper. In this step, the hot-pressed carbon paper is carbonized in a high-temperature tube furnace with a heating rate of 10℃ / min, a sintering temperature of 1100℃, and a holding time of 1 hour. After cooling, the carbonized carbon paper is taken out and is called CNFM-PF / CP-0.4.
[0053] Before grafting CNF onto methyl acrylate monomer, carbon paper base paper, phenolic resin, 99% ethanol and CNF are required. The CNF is commercially available and is usually prepared by mechanical methods. Bleached coniferous pulp is pretreated with cellulase and then homogenized by a high-pressure homogenizer. The carbon nanofibers have a length of 1-5 μm and a diameter of 10-20 nm.
[0054] Example 2: A method for preparing highly conductive and highly porous carbon paper for proton exchange membrane fuel cells, comprising the following steps:
[0055] S1. CNF is grafted onto methyl acrylate monomer to obtain CNF-grafted methyl acrylate. In this step, the process of grafting CNF onto methyl acrylate monomer involves taking 10 portions of CNF (carbon nanofibers) by dry weight, diluting them with deionized water to a mass concentration of 2%, and adding them to a three-necked flask equipped with a stirrer. The three-necked flask is placed in a 30°C constant temperature water bath, and the pH of the CNF suspension is adjusted to 1.0 with 20% nitric acid. Next, cerium ammonium nitrate is added to the suspension at a concentration of 5.0 mmol / L (relative to the total system volume), and then the mixture is stirred at 500 rpm. After stirring evenly under the conditions, nitrogen gas was introduced for 30 minutes to remove oxygen from the reaction system. Finally, methyl acrylate monomer was added dropwise using a peristaltic pump for graft polymerization. The reaction was terminated after 2 hours. After the reaction was completed, the solid and liquid were separated by centrifugation at 10,000 rpm and 4°C for 15 minutes. After solid-liquid separation, the solid was first washed with deionized water until neutral to remove the initiator and acid. The washed solid was subjected to Soxhlet extraction for 24 hours using a mixture of acetone and tetrahydrofuran at a ratio of 1:2 to remove the homopolymer. The obtained solid was CNF-grafted methyl acrylate.
[0056] S2. Prepare a mixed solution of phenolic resin and ethanol solution. Add CNF-grafted methyl acrylate to the mixed solution and stir ultrasonically to obtain an adhesive. Then, impregnate carbon paper with the solution and sonicate it. After removing the carbon paper, lay it flat to obtain a preform. In this step, ethanol solution is used as a solvent. After adding phenolic resin, a mixed solution with a phenolic resin concentration of 12 wt% is prepared. CNF-grafted methyl acrylate is added to obtain a mixed solution with a CNF-grafted methyl acrylate mass concentration of 0.8%. Then, the mixed solution is sonicated for 10 min to ensure uniform dispersion in the mixed solution. This solution is stored as an adhesive. Then, carbon paper is impregnated with the solution and sonicated for 20 min. After removing the paper, it is laid flat with a glass rod to ensure uniform resin penetration. This solution is used as a preform.
[0057] S3. The preform is dried in an oven to obtain dried carbon paper, and then compressed and formed by hot pressing in a vulcanizing bed to obtain hot-pressed carbon paper base paper (HPCP); in this step, the drying time in the oven is one hour and the temperature is 80°C; the vulcanizing bed is hot-pressed in air at a temperature of 150°C and a pressure of 4MPa for 1 hour.
[0058] S4. The hot-pressed carbon paper base paper is carbonized in a high-temperature tube furnace, and finally cooled to obtain carbonized carbon paper. In this step, the hot-pressed carbon paper is carbonized in a high-temperature tube furnace with a heating rate of 10℃ / min, a sintering temperature of 1100℃, and a holding time of 1 hour. After cooling, the carbonized carbon paper is taken out and is called CNFM-PF / CP-0.8.
[0059] Example 3: A method for preparing highly conductive and highly porous carbon paper for proton exchange membrane fuel cells, comprising the following steps:
[0060] S1. CNF is grafted onto methyl acrylate monomer to obtain CNF-grafted methyl acrylate. In this step, the process of grafting CNF onto methyl acrylate monomer involves taking 10 portions of CNF (carbon nanofibers) by dry weight, diluting them with deionized water to a mass concentration of 2%, and adding them to a three-necked flask equipped with a stirrer. The three-necked flask is placed in a 30°C constant temperature water bath, and the pH of the CNF suspension is adjusted to 1.0 with 20% nitric acid. Next, cerium ammonium nitrate is added to the suspension at a concentration of 5.0 mmol / L (relative to the total system volume), and then the mixture is stirred at 500 rpm. After stirring evenly under the conditions, nitrogen gas was introduced for 30 minutes to remove oxygen from the reaction system. Finally, methyl acrylate monomer was added dropwise using a peristaltic pump for graft polymerization. The reaction was terminated after 2 hours. After the reaction was completed, the solid and liquid were separated by centrifugation at 10,000 rpm and 4°C for 15 minutes. After solid-liquid separation, the solid was first washed with deionized water until neutral to remove the initiator and acid. The washed solid was subjected to Soxhlet extraction for 24 hours using a mixture of acetone and tetrahydrofuran at a ratio of 1:2 to remove the homopolymer. The obtained solid was CNF-grafted methyl acrylate.
[0061] S2. Prepare a mixed solution of phenolic resin and ethanol solution. Add CNF-grafted methyl acrylate to the mixed solution and stir ultrasonically to obtain an adhesive. Then, impregnate carbon paper with the solution and sonicate it. After removing the carbon paper, lay it flat to obtain a preform. In this step, ethanol solution is used as a solvent. After adding phenolic resin, a mixed solution with a phenolic resin concentration of 12 wt% is prepared. CNF-grafted methyl acrylate is added to obtain a mixed solution with a CNF-grafted methyl acrylate mass concentration of 1.2%. Then, the mixed solution is sonicated for 10 min to ensure uniform dispersion in the mixed solution. This solution is stored as an adhesive. Then, carbon paper is impregnated with the solution and sonicated for 20 min. After removing the paper, it is laid flat with a glass rod to ensure uniform resin penetration. This solution is used as a preform.
[0062] S3. The preform is dried in an oven to obtain dried carbon paper, and then compressed and formed by hot pressing in a vulcanizing bed to obtain hot-pressed carbon paper base paper (HPCP); in this step, the drying time in the oven is one hour and the temperature is 80°C; the vulcanizing bed is hot-pressed in air at a temperature of 150°C and a pressure of 4MPa for 1 hour.
[0063] S4. The hot-pressed carbon paper base paper is carbonized in a high-temperature tube furnace, and finally cooled to obtain carbonized carbon paper. In this step, the hot-pressed carbon paper is carbonized in a high-temperature tube furnace with a heating rate of 10℃ / min, a sintering temperature of 1100℃, and a holding time of 1 hour. After cooling, the carbonized carbon paper is taken out and is called CNFM-PF / CP-1.2.
[0064] Example 4: A method for preparing highly conductive and highly porous carbon paper for proton exchange membrane fuel cells, comprising the following steps:
[0065] S1. CNF is grafted onto methyl acrylate monomer to obtain CNF-grafted methyl acrylate. In this step, the process of grafting CNF onto methyl acrylate monomer involves taking 10 portions of CNF (carbon nanofibers) by dry weight, diluting them with deionized water to a mass concentration of 2%, and adding them to a three-necked flask equipped with a stirrer. The three-necked flask is placed in a 30°C constant temperature water bath, and the pH of the CNF suspension is adjusted to 1.0 with 20% nitric acid. Next, cerium ammonium nitrate is added to the suspension at a concentration of 5.0 mmol / L (relative to the total system volume), and then the mixture is stirred at 500 rpm. After stirring evenly under the conditions, nitrogen gas was introduced for 30 minutes to remove oxygen from the reaction system. Finally, methyl acrylate monomer was added dropwise using a peristaltic pump for graft polymerization. The reaction was terminated after 2 hours. After the reaction was completed, the solid and liquid were separated by centrifugation at 10,000 rpm and 4°C for 15 minutes. After solid-liquid separation, the solid was first washed with deionized water until neutral to remove the initiator and acid. The washed solid was subjected to Soxhlet extraction for 24 hours using a mixture of acetone and tetrahydrofuran at a ratio of 1:2 to remove the homopolymer. The obtained solid was CNF-grafted methyl acrylate.
[0066] S2. Prepare a mixed solution of phenolic resin and ethanol solution. Add CNF-grafted methyl acrylate to the mixed solution and stir ultrasonically to obtain an adhesive. Then, impregnate carbon paper with the solution and sonicate it. After removing the carbon paper, lay it flat to obtain a preform. In this step, ethanol solution is used as a solvent. After adding phenolic resin, a mixed solution with a phenolic resin concentration of 12 wt% is prepared. CNF-grafted methyl acrylate is added to obtain a mixed solution with a CNF-grafted methyl acrylate mass concentration of 1.6%. Then, the mixed solution is sonicated for 10 min to ensure uniform dispersion in the mixed solution. This solution is stored as an adhesive. Then, carbon paper is impregnated with the solution and sonicated for 20 min. After removing the paper, it is laid flat with a glass rod to ensure uniform resin penetration. This solution is used as a preform.
[0067] S3. The preform is dried in an oven to obtain dried carbon paper, and then compressed and formed by hot pressing in a vulcanizing bed to obtain hot-pressed carbon paper base paper (HPCP); in this step, the drying time in the oven is one hour and the temperature is 80°C; the vulcanizing bed is hot-pressed in air at a temperature of 150°C and a pressure of 4MPa for 1 hour.
[0068] S4. The hot-pressed carbon paper base paper is carbonized in a high-temperature tube furnace, and finally cooled to obtain carbonized carbon paper. In this step, the hot-pressed carbon paper is carbonized in a high-temperature tube furnace with a heating rate of 10℃ / min, a sintering temperature of 1100℃, and a holding time of 1 hour. After cooling, the carbonized carbon paper is taken out and is called CNFM-PF / CP-1.6.
[0069] Example 5: The steps in this example are the same as in Example 4, but in step 2, ethanol solution is used as the solvent. After adding phenolic resin, a mixed solution with a phenolic resin concentration of 12 wt% is prepared. Different proportions of CNF-grafted methyl acrylate are added to obtain mixed solutions with CNF-grafted methyl acrylate mass concentrations of 0%, 0.4%, 0.8%, 1.2%, and 1.6%. Finally, after cooling, carbonized carbon paper is obtained, which is respectively called...
[0070] CP, CNFM-PF / CP-0.4, CNFM-PF / CP-0.8, CNFM-PF / CP-1.2, CNFM-PF / CP-1.6.
[0071] To further illustrate the technical solution of the present invention,
[0072] The following tests were conducted on CP, CNFM-PF / CP-0.4, CNFM-PF / CP-0.8, CNFM-PF / CP-1.2, and CNFM-PF / CP-1.6 to analyze their performance, with CP serving as the control group.
[0073] 1. First, the porosity, pore size distribution, and air permeability of the carbonized paper were analyzed. A mercury porosimeter (Autopore V9620) was used to measure the internal pores of the carbonized paper. The mercury porosimetry method was used to measure the interconnected porosity and pore size distribution of the sample in detail, which reflects the ease with which internal gas can enter and be expelled. Then, an air permeability meter (FX3000) was used to analyze the air permeability of the carbonized paper base. The base paper was placed on the stage of the air permeability meter, and a test area of 20 cm² was selected. 2 The test pressure was set to 200 Pa. The analysis was performed according to the instrument's operating instructions. After the instrument reading stabilized, the data was recorded. The air permeability of each sample was tested at least 5 times, and the average value was taken to obtain the air permeability of the sample.
[0074] 2. The mechanical properties of the carbon paper were tested using a general mechanical testing machine. The tensile strength was tested using the ASTM D828 standard with a loading rate of 10 mm / min, and the average value was taken from five different readings. The flexural strength was measured using a three-point bending test with a span length of 30 mm and a descent rate of 0.5 mm / min. The dried carbon paper was then visualized under a SU1510 scanning electron microscope. The scanning electron microscope images provided information on the thickness, morphology, and carbon fiber layout of the carbon paper.
[0075] 3. Use a four-probe tester (RTS-8 type) to determine the planar resistivity of carbon paper. Test at least 10 points for each sample, measure and take the average value, which is the resistivity of the sample.
[0076] For battery performance analysis, using carbon paper as the gas diffusion layer in a proton exchange membrane fuel cell requires cutting it into pieces with an area of 2*2cm. 2 The blocks were then used in 3*3cm format. 2 A catalytic coating membrane (CCM) was used to form a three-layer membrane electrode assembly. The CCM thickness was 45 μm, and the catalyst Pt / C anode loading was 0.12 mg / cm³. 2 The cathode concentration is 0.48 mg / cm². 2 This invention primarily studies the influence of carbon paper as a conductive carbon material. It does not involve microporous layer treatment of the carbon paper, nor does it involve hot-pressing of CNFM and carbon fiber paper. Instead, the same torsional force is used during fuel cell assembly to ensure tight contact between the layers. The membrane electrode assembly was placed within a fuel cell testing system. The activation area is 4 cm². 2 The bipolar plate is a serpentine flow channel graphite plate made of highly compacted graphite. The gas flow rate at the anode is 200cc / min (humidifier temperature is maintained at 60℃), and the gas flow rate at the cathode is 300cc / min (humidifier temperature is maintained at 40℃). The battery temperature during the test is set to 65℃.
[0077] After a series of experiments, results were obtained and discussed. During the impregnation process of carbon paper preparation, the poor compatibility between phenolic resin and the carbon paper base paper hindered the formation of the required interfacial adhesion. While CNF modification of the phenolic resin was attempted, uneven dispersion remained a problem. The experiment demonstrated that grafting methyl acrylate (MMA) onto CNF significantly improved the dispersibility of CNF in PF solution. A conceptual diagram of the grafting process is attached. Figure 1 As shown; the dispersion effect of grafted MMA CNF (CNFM) is as follows. Figure 2As shown, it can be directly observed that CNF tends to aggregate in PF solution, resulting in numerous flocculent clumps in the dispersed solution. Compared to CNF, grafted CNF disperses well in PF solution, and the pure PF solution is relatively clear. However, as CNFM is added from 0 to 1.6 wt%, the color of CNFM-PF gradually deepens. Secondly, evaluating the hydrophilicity / hydrophobicity of CNF and CNFM using contact angles explains why grafted MMA CNF is uniformly dispersed in PF solution. Before measuring the contact angles, CNF was dried in a forced-air drying oven, as shown in the attached diagram. Figure 3 and 4 As shown, the contact angle of unmodified CNF is 14.2°. However, after grafting MMA onto the CNF surface, the contact angle increases to 123.4°, indicating that CNFM is hydrophobic and can be better dispersed in PF solution (free radical graft copolymerization of nanofiberized cellulose and acrylic monomers). Furthermore, the properties of CNFM were evaluated using Fourier transform infrared spectroscopy and TGA, as shown in the attached figure. Figure 5 As shown, CNF and CNFM first exhibit cellulose functional groups, 3400 cm⁻¹ -1 The broad band at [value] is a typical characteristic peak of dehydroglucose units, and in the CNFM spectrum, it is located at approximately 2950, 1740, and 1260 cm⁻¹. -1 New peaks were observed at the [specific locations], corresponding to the asymmetric stretching vibration of methyl groups, the C=O vibration, and the CO stretching of ester groups, respectively. This indicates the green functionalization in cellulose nanocrystal-reinforced polynanocomposites, exhibiting the nanostructural effect of high-cellulose-content thermoplastic nanocomposites with covalently grafted cellulose-MMA interfaces. The thermal stability of CNF and CNFM was characterized by TG and DTG, as shown in the attached figure. Figure 6 As shown in the TGA analysis, the initial thermal decomposition temperatures of CNF and CNFM were 144℃ and 216℃, respectively, while the decomposition temperatures at the maximum weight loss rate were 335℃ and 407℃, respectively, indicating that CNF-MMA exhibited higher thermal stability. Furthermore, compared to the TSI stability index of pure PF, the TSI stability index of CNFM-PF-0.4 increased to 31.76, significantly higher than PF's 0.94. With increasing CNFM proportion, the TSI stability index decreased accordingly. When the CNFM proportion increased by 1.6 wt%, the stability of the modified PF solution was greatly improved, with its TSI stability index decreasing to 1.57, similar to the TSI stability index of the PF solution (0.94). In conclusion, with a certain increase in the proportion of MMA in PF, the dispersion stability is significantly improved, allowing for uniform dispersion in the PF impregnation solution.
[0078] As attached Figure 7 (a) to Figure 7As shown in (e), this figure illustrates the surface microstructure of hot-pressed carbon paper base paper with CNFM added at proportions of 0, 0.4 wt%, 0.8 wt%, 1.2 wt%, and 1.6 wt% to a mixed solution of phenolic resin and ethanol. The figure shows that the unmodified CP surface has a relatively small impregnation amount, and PF is easily lost after hot pressing, resulting in uneven distribution. However, as the CNFM proportion increases, the PF impregnation amount on the carbon paper base paper surface continuously increases. Notably, when the CNFM content increases to 1.6 wt%, the surface of the carbon paper base paper (CPBP) is almost completely covered by the impregnation solution and can adhere relatively uniformly to the CP. The mass of the carbon paper base paper after hot pressing gradually increases from 0.927 g (unmodified carbon paper) to 1.128 g (1.6 wt% CNFM modified carbon paper). (See attached figure.) Figure 7 As shown in (f), PF modified with 1.6 wt% CNFM better encapsulates the carbon fibers, thus forming a good interfacial bond between the carbon fibers and PF during the hot pressing stage. This suggests that the addition of CNFM increases the impregnation amount of the carbon paper during the hot pressing stage, allowing more PF to remain on the CP. This may be because CNFM exhibits a network structure, which effectively restricts PF flow, thereby reducing the loss of impregnation liquid during hot pressing and enabling more complete curing and crosslinking.
[0079] As attached Figure 8 The diagram shows the air permeability of carbon paper with different proportions of CNFM. It can be seen that when impregnated with unmodified PF, the air permeability of the carbon paper after hot pressing is 1080 L / m² / s. When the CNFM-modified PF proportion is 1.6 wt%, the surface of the carbon paper is almost completely covered, and the air permeability drops to a minimum of only 255 L / m² / s, a reduction of 76%. This is also evidenced by the appearance photos of the hot-pressed carbon paper (left) and the hot-pressed carbon paper modified with 1.6 wt% CNFM (right). Therefore, it can be concluded that the addition of CNFM can reduce the air permeability of CPBP, allowing more PF to remain on the CP. This is because the modified PF is less prone to loss, and during the hot pressing process, a large number of pores in the carbon paper are filled by PF, leading to a gradual decrease in air permeability.
[0080] As attached Figure 9 As shown in the figure, this is the stress-strain curve, used to study the mechanical properties of the modified carbon paper base. The results show that the tensile strength of the carbon paper base significantly improves after the addition of CNFM, with the optimal addition amount being 1.6 wt%. The corresponding tensile strength of the modified carbon paper base is 30.54 MPa, significantly higher than that of pure PF carbon paper base (18.86 MPa), an increase of 62%. This indicates that the addition of CNFM can improve the interfacial bonding between the carbon paper base and PF, allowing a large amount of impregnating solution to remain on the CP, thereby increasing the tensile strength of the carbon paper base. This result can be explained by the high mechanical and tensile strength of CNFM.
[0081] Impregnation with PF has a certain enhancing effect on the resistivity of carbon paper base paper. This can be explained by the fact that uncarbonized phenolic resin does not have a six-carbon ring structure and therefore does not have conductivity. After adding CNFM, carbon paper modified with different proportions of CNFM exhibits different planar resistivity. First, with the increase of CNFM proportion, the planar resistivity increases significantly, as shown in the attached figure. Figure 10 As shown, compared with pure PF-impregnated carbon paper (225.33 mΩ·cm), the planar resistivity of carbon paper modified with 1.6 wt% M is 332.87 mΩ·cm, an increase of nearly 48%. Therefore, it can be inferred that the increase in PF impregnation leads to the increase in resistivity.
[0082] As attached Figure 11 As shown in the figure, the mass loss of TG indicates that the CP impregnation with pure PF has the smallest mass loss (29.88%). With the increase of the proportion of M added to PF, the carbon paper base paper modified with 1.6 wt% CNFM experienced a mass loss of 33.34% after pyrolysis, as shown in the attached figure. Figure 10 As shown, the CNFM-modified carbon paper base paper has a lower carbon residue rate, which is in good agreement with the thermogravimetric results of PF and CNFM-PF. It is worth noting that, from the attached... Figure 8 The DTG analysis shows two peaks in the 400℃-600℃ range. The carbon paper impregnated with pure PF exhibits lower pyrolysis rates at both peaks. However, with increasing CNFM content in PF, the carbon paper modified with 1.6wt% CNFM shows significantly higher peak values (-0.086 and -0.099) compared to the unmodified carbon paper (-0.077 and 0.087). This further demonstrates that the addition of CNFM increases the pyrolysis rate of PF in the 400℃-600℃ range. This can be explained by the poor thermal stability of CNFM, which rapidly decomposes into volatile substances within this temperature range.
[0083] The carbonization process has a profound impact on the evolution of CP porous structures, from Figure 12 As can be seen in (b), the unmodified CP after carbonization has a macroporous structure, as shown in the attached figure. Figure 12 (c) shows that the surface of the matrix carbon is smooth; the overall pore size of the CNFM-modified CP is relatively uniform, and the pore size distribution on the surface is small. Notably, many uniform micropores were found on the matrix carbon, such as... Figure 12 As shown in (f), this may be due to the release of volatile substances during CNFM pyrolysis, resulting in micropores (consistent with the thermogravimetric and thermal product release patterns described above in the 400-600℃ temperature range). The release of volatile substances during pyrolysis transforms into a porous carbon structure, leading to a rougher surface and the formation of numerous shallow nanopores on the pore walls. Figure 12(e) It can be seen that the microstructure of CNFM-modified CP has a large amount of matrix carbon adhering to the surface of the carbon paper. This may be due to the following reasons: Firstly, the network structure formed by the addition of CNFM during hot pressing restricts the loss of PF, as shown in the attached image. Figure 7 As shown in (e), this allows more matrix carbon to adhere to the CP surface after carbonization; on the other hand, the addition of CNFM at the high-temperature stage inhibits the breakage of PF and helps to generate more semi-coke, enabling the matrix carbon and carbon fibers to adhere more tightly during carbonization, increasing the adhesion amount, such as... Figure 12 (d) and Figure 12 (e) However, during the carbonization process of unmodified carbon paper, due to the drastic decomposition and shrinkage of PF, the rapid release of products (corresponding to the release pattern generated by thermal depolymerization) leads to significant interfacial separation. The matrix carbon is difficult to adhere to the smooth fiber surface, and the interfacial bonding strength becomes very weak, as shown in the attached image. Figure 12 As shown in (a).
[0084] The cross-sectional profiles of CP and CNFM-PF / CP were characterized using scanning electron microscopy. It can be seen that the thickness of the carbon paper gradually decreases with increasing CNFM ratio. During the drying, hot-pressing, and carbonization stages, the mass of the carbon paper gradually increases as the CNFM ratio increases from 0 to 1.6 wt%, as shown in the attached figure. Figure 13 As shown, the mass of the carbonized paper gradually increased from 0.7g to 0.809g. Notably, the density of the carbon paper increased linearly with different CNFM ratios. Compared to unmodified carbon paper (0.32g / cc), the bulk density of carbon paper modified with 1.6wt% CNFM was 0.48g / cc, an increase of 50%, as shown in the attached figure. Figure 14 As shown, since other dimensions remain consistent, the increase in density can be attributed to the linear decrease in carbon paper thickness with increasing CNFM ratio. The carbon paper thickness gradually increases from 0.173 mm in unmodified carbon paper to 0.137 mm in 1.6 wt% CNFM-modified carbon paper, a reduction of nearly 21%. This is likely due to the matrix shrinking towards the carbon fiber surface after carbonization, resulting in excessive shrinkage and strong matrix carbon / carbon fiber interaction, thus reducing the CP thickness and consequently increasing the carbon paper density.
[0085] Mass transport in fuel cells largely depends on the porosity and pore size distribution of the carbon electrode support, while mass transport in the carbon paper is primarily determined by diffusion mechanisms. Current density is largely determined by the diffusion flux of reactants to the catalyst layer (or from the catalyst layer to the flow field). CT images directly reveal the pore structure of the internal carbon paper. Figure 15As shown in (a), the interfacial bonding between the carbon matrix and carbon fibers in CT images of carbon paper is relatively weak. Compared with unmodified CP, the addition of 1.6 wt% CNFM results in more carbon matrix adhering to the carbon fibers on the surface of the modified carbon paper, as shown in the figure. Figure 15 As shown in (b). Furthermore, from... Figure 15 (c) and Figure 15 As shown in (d), the distribution of matrix carbon within the carbon paper and its bonding with carbon fibers are evident. Unmodified CP matrix carbon exhibits a blocky and uneven distribution, easily causing pore blockage. However, with the addition of CNFM, the matrix carbon becomes network-like. This is likely because the CNFM network structure effectively restricts PF flow, allowing the matrix carbon to remain more fully within the carbon fibers during pyrolysis, thus improving the fiber / matrix interface bonding. Furthermore, the matrix carbon surface has numerous microporous structures; the release of volatile substances from CNFM-modified PF during pyrolysis leads to increased internal pore size.
[0086] As attached Figure 16 As shown, the changes in pore size distribution after carbonization of carbon paper with different proportions of CNFM were obtained by mercury porosimetry. The results show that for CNFM-modified CP, as the CNFM proportion increased from 0.4 wt% to 1.6 wt%, the pore size distribution shifted towards smaller pores, resulting in a narrower overall pore size distribution, with most pores ranging from 10 to 50 μm. However, for CP, the pore size distribution was mostly in the 40-70 μm diameter range. Furthermore, as shown in the attached figure... Figure 17 As shown, the interconnected porosity of the carbon paper gradually increased from 77.16% (unmodified CP) to 82.26% (1.6wt% CNFM-modified CP). The reasons for this are as follows: Firstly, during the carbonization process, the residual char rate of CNFM is low (which is consistent with the TG results of the carbon paper and the CNFM-modified carbon paper). As the pyrolysis temperature increases, the evolution of volatile substances generates pores, and the decomposition of CNFM produces some micropores. Secondly, reducing the CP thickness reduces the possibility of pore blockage, decreases the number of isolated pores, and forms good pore connectivity within the carbon paper. Pore connectivity and uniform pore size distribution are ideal choices for a good fuel cell electrode, making the entire electrode area electrochemically active. The permeability of the prepared carbon paper is as follows: Figure 17 As shown, with the CNFM ratio increasing from 0 to 1.6 wt%, the air permeability of the carbon paper gradually increased from 1410 L / m² / s to 2876 L / m² / s, which is 104% higher than that of the unmodified CP. Although the unmodified carbon paper has less matrix carbon, its pore connectivity is low, indicating blockage and a large number of isolated pores. As expected, with the increase of the CNFM ratio, the pore connectivity is increased and the residual carbon content is low, providing more channels for gas diffusion, and ultimately the gas permeability also increases.
[0087] The amorphous properties of CP and CNFM-modified CP were revealed by X-ray diffraction patterns, such as... Figure 18 As shown in (a), all samples exhibit two diffraction peaks at 26° and 45°, located on the (002) and (101) planes, respectively. The results indicate that CP exhibits typical non-static characteristics regardless of the CNFM addition ratio. As the CNFM addition ratio increases from 0 to 1.6 wt%, the two distinct diffraction peaks change slightly. With the gradual increase in the CNFM addition ratio, the intensity of the (002) plane diffraction peak at 26° (2θ) decreases sharply, while the peak intensity of the (101) plane at 45° remains unchanged. These results suggest that the change in the CP crystal structure is related to the addition of CNFM, which is consistent with the results showing that CNFM inhibits PF molecular chain breakage during high-temperature pyrolysis.
[0088] To further investigate the surface composition and chemical state of these CP materials, X-ray photoelectron spectroscopy analysis was performed, based on... Figure 18 As shown in (b), the relative atomic content was calculated, and the oxygen content in the carbon paper with 1.6 wt% CNFM was 15.14%, significantly higher than the oxygen content in CP (6.59%). This result can be attributed to the fact that more matrix carbon remained on the carbon fibers. Compared to CP, the oxygen-to-carbon ratio (O / C) increased from 0.07 to 0.18 with the addition of 1.6 wt% CNFM, indicating that the addition of CNFM introduced abundant oxygen atoms. High-resolution X-ray photoelectron spectra of the C1s and O1s peaks are shown below. Figure 18 As shown in (cf). Carbon materials typically consist of two types of carbon atoms, namely basal and sp. 2 and defects sp 3 sp 3 The content of carbon atoms can reflect the defect level. The high-resolution C1s spectrum shows three peaks at 284.8, 285.9, and 289.5 eV, representing different carbon bonds, corresponding to trigonal carbon (sp...). 2 Central carbon, tetrahedral carbon (sp) 3 (Center) and π-π*. High-resolution C1s spectra of CP and CNFM-PF / CP-1.6 show that the carbon paper modified with 1.6 wt% CNFM contains sp... 3 The carbon content has increased. Compared to CP, the carbon paper modified with 1.6 wt% CNFM has a higher sp... 3 / sp 2The value increased from 0.16 to 0.39, indicating that CNFM-PF / CP-1.6 has more defects, which is consistent with the results of the X-ray diffraction pattern. In summary, CNFM-modified PF forms new structures on CP, such as defects and functional groups, including π-π* covalent bonds. In addition, high-resolution XPS O1 shows four peaks (531.6, 532.6, 533.8, and 535.0 eV). The peak at 531.6 eV represents the carboxyl group (COO-) and the oxygen-carbon double bond (O=CO) in the carboxylate. The peak at 532.6 eV corresponds to the hydroxyl (C-OH) and carbonyl (C=O) functional groups. The peaks at 533.8 eV and 535.0 eV represent the ester and carboxylic acid (O=CO) and the oxygen single bond in chemisorbed oxygen or water (HOH), respectively. The high-resolution XPS spectrum of the O1s peak shows that the content of -OH groups on CNFM-PF / CP-1.6 is significantly higher than that on CP, and compared with other functional groups, -OH groups also have more electrochemically active sites. Therefore, the abundant functional group CP enhances the wettability and electrocatalytic activity.
[0089] like Figure 18 As shown in (g), the resistivity of carbon paper was characterized using a four-probe method. After carbonization, the resistivity of CP decreased with increasing CNFM ratio. The planar resistivity of CP modified with 1.6 wt% CNFM decreased to 3.27 mΩ·cm, a 26% reduction compared to unmodified CP (4.44 mΩ·cm). The results indicate that the resistivity of CP gradually decreases with increasing CNFM ratio. This may be due to the reduced sample thickness and increased bulk density, resulting in shorter conductive pathways. Furthermore, good interfacial bonding also reduces the resistivity of CP. As mentioned above, increasing the CNFM ratio enhances the interfacial bonding of CP, thereby improving carrier transport between the matrix carbon and carbon fibers, providing more electron transport pathways, and reducing the resistivity of the carbon paper. This demonstrates that the addition of CNFM can provide lower resistivity for CP.
[0090] from Figure 18 (h) It can be seen that the flexural strength of carbon paper increases with the increase of CNFM ratio, reaching a peak (348.6 MPa) when 1.2 wt% CNFM is added, which is nearly 3 times higher than the flexural strength of unmodified CP (87.5 MPa). Further addition of CNFM to 1.6 wt% causes the flexural strength of CP to begin to decrease to 222.97 MPa. The results show that the addition of CNFM can improve the flexural strength of CP, but the decrease in flexural strength of CP modified with 1.6 wt% CNFM may be related to its porosity and pore size distribution. Larger pores may act as crack initiators, and cracks may preferentially propagate through these larger pores, leading to CP failure and its lower strength value, which in turn leads to the decrease in CP flexural strength.
[0091] from Figure 18 (i) It can be seen that the tensile strength gradually increases with the addition of CNFM, and high tensile strength is crucial for the supporting effect of carbon paper. The tensile strength of carbon paper modified with 1.6 wt% CNFM (12.06 MPa) is 72.78% higher than that of unmodified CP (6.98 MPa). The results indicate that the addition of CNFM helps to improve the mechanical strength of CP. This result can be explained by the following: on the one hand, the volatilization of CNFM molecules during pyrolysis leads to an increase in micropores (<10 μm), and the overall pore size decreases, forming a buffer structure as a matrix shrinkage. Such a structure can minimize stress concentration centers and provide a medium to limit crack propagation. On the other hand, the matrix carbon adheres better to the carbon fibers, and the two are tightly connected, resulting in enhanced interfacial strength of CP. The enhanced interfacial structure has a bridging effect on load transfer and stress relaxation, thereby improving the mechanical strength of modified CP.
[0092] To investigate the performance achieved using modified materials during operation, a 4cm [scale / test] was performed. 2 Effective unit PEMFC field tests yielded the current density and corresponding output power density generated by the polarization curves of CP with five different CNFM ratios (0, 0.4wt%, 0.8wt%, 1.2wt%, and 1.6wt%), as shown in the attached figure. Figure 19 The peak power densities of CNFM-PF / CP-0.4, CNFM-PF / CP-0.8, CNFM-PF / CP-1.2, and CNFM-PF / CP-1.6 are 209, 232, 267, 289, and 325 mW / cm², respectively. 2 The superior performance of CP modified with 1.6 wt% CNFM is due to its better porosity, while simultaneously providing effective conductivity and the required strength. Two main factors influence fuel cell performance: first, the conductivity of CP; CNFM concentration reduces CP thickness, increases its bulk density, and forms shorter conductive pathways, thus reducing the resistivity of the carbon paper; second, gas permeability, with current density largely determined by the diffusion flux of reactants to the catalyst layer (or from the catalyst layer to the flow field). Permeability increases with decreasing thickness, following the same trend as porosity, due to the decrease in gas diffusion length with decreasing sample thickness. Furthermore, during pyrolysis, the release of volatile CNFM substances introduces abundant micropores (<20 μm), forming a uniform pore size distribution. The CNFM-modified CP also improves internal interconnected porosity, facilitating reactant gas diffusion and leading to performance enhancement. On the other hand, electrochemical impedance spectroscopy (EIS) of the fuel cell, as shown in the attached figure, further enhances performance. Figure 20As shown, the arc size measured by EIS reflects the concentration loss of the fuel cell in the high current density and low frequency range. It can be seen that as the CNFM ratio increases, the arc of CNFM-PF / CP is smaller than that of CP at low frequency. This indicates that CNFM-PF / CP has better material transport capacity. This is because CNFM-PF / CP has a more reasonable pore size distribution. Therefore, CNFM-PF / CP has better fuel cell performance than CP.
[0093] In summary, highly conductive and highly porous carbon paper was successfully prepared by modifying phenolic resin with methyl acrylate grafted onto nanocellulose, which can be used in practical applications of proton exchange membrane fuel cells. When 1.6 wt% CNF grafted onto methyl acrylate was added, the tensile strength of the carbonized CNFM-PF / CP (12.1 MPa) was increased by 75% compared to CP (6.9 MPa), therefore CNFM-PF / CP-1.6 is preferred. Furthermore, the modified carbon paper exhibits good flexibility while maintaining its conductivity. Single-cell evaluation of the modified carbon paper showed that the performance of the cell composed of NFM-PF / CP-1.6 (H2-air) was the best, with a limiting power density of 325.42 mW / cm2 at a humidification temperature of 60°C, which is 55% higher than that of CP (209.55 mW / cm2). These modified novel CPs possess high conductivity, uniform pore size distribution, and low charge transfer impedance, which can improve the performance of fuel cells.
Claims
1. A method for preparing highly conductive and highly porous carbon paper for proton exchange membrane fuel cells, characterized in that: Includes the following steps: S1. CNF is grafted onto methyl acrylate monomer to obtain CNF-grafted methyl acrylate. S2. Prepare a mixed solution of phenolic resin and ethanol solution, add CNF-grafted methyl acrylate to the mixed solution, and stir ultrasonically to obtain an adhesive; then impregnate the carbon paper base paper in it and perform ultrasonic treatment, remove the carbon paper base paper and lay it flat to obtain a preform; S3. The preform is dried in an oven to obtain dried carbon paper, which is then compressed and molded by hot pressing in a vulcanizing bed to obtain hot-pressed carbon paper base paper. S4. The hot-pressed carbon paper base paper is carbonized in a high-temperature tube furnace, and finally cooled to obtain carbonized carbon paper.
2. The method for preparing high-conductivity, high-porosity carbon paper for proton exchange membrane fuel cells according to claim 1, characterized in that: In step S1, the process of grafting CNF with methyl acrylate monomer involves taking 5-15 parts of CNF by dry weight, diluting it with deionized water to a mass concentration of 1-5%, and placing it in a constant temperature water bath at 25-35℃. The pH of the CNF suspension is adjusted to 0.8-1.5 with nitric acid. Next, cerium ammonium nitrate is added to the suspension at a concentration of 5.0 mmol / L. After stirring evenly at a speed of 400-600 rpm, nitrogen gas is introduced for 30 minutes to remove oxygen from the reaction system. Finally, methyl acrylate monomer is added dropwise using a peristaltic pump for graft polymerization. The reaction is terminated after 1.5-2.5 hours. After the reaction is completed, the solid is separated by centrifugation at a speed of 8000-12000 rpm and a temperature of 3-5℃ for 10-20 minutes. The obtained solid is CNF-grafted methyl acrylate.
3. The method for preparing high-conductivity, high-porosity carbon paper for proton exchange membrane fuel cells according to claim 2, characterized in that: In step S1, the process of grafting CNF with methyl acrylate monomer involves taking 10 portions of CNF by dry weight, diluting them with deionized water to a mass concentration of 2%, and placing them in a 30°C constant temperature water bath. The pH of the CNF suspension is adjusted to 1.0 with nitric acid. Next, cerium ammonium nitrate is added to the suspension at a concentration of 5.0 mmol / L. After stirring evenly at 500 rpm, nitrogen gas is introduced for 30 minutes to remove oxygen from the reaction system. Finally, methyl acrylate monomer is added dropwise using a peristaltic pump for graft polymerization. The reaction is terminated after 2 hours. After the reaction is completed, the solid is separated by centrifugation at 10,000 rpm and 4°C for 15 minutes. The obtained solid is CNF-grafted methyl acrylate.
4. The method for preparing high-conductivity, high-porosity carbon paper for proton exchange membrane fuel cells according to claim 1 or 2, characterized in that: After solid-liquid separation, the solid was first washed with deionized water until neutral to remove the initiator and acid. The washed solid was then subjected to Soxhlet extraction for 24 hours using a mixture of acetone and tetrahydrofuran at a ratio of 1:2 to remove the homopolymer.
5. The method for preparing high-conductivity, high-porosity carbon paper for proton exchange membrane fuel cells according to claim 1, characterized in that: In step 2, phenolic resin is added to an ethanol solution to prepare a mixed solution with a phenolic resin concentration of 12 wt%. CNF-grafted methyl acrylate is then added to obtain a mixed solution with a CNF-grafted methyl acrylate mass concentration of 0.2-1.8%. The mixed solution is then ultrasonically stirred for 8-15 minutes to ensure uniform dispersion in the mixed solution. This solution is then stored as an adhesive. Carbon paper is then impregnated in the solution and ultrasonically treated for 15-25 minutes. After removal, it is spread evenly with a glass rod to ensure uniform resin penetration. This is then used as a preform.
6. The method for preparing high-conductivity, high-porosity carbon paper for proton exchange membrane fuel cells according to claim 5, characterized in that: The mixed solution has a CNF-grafted methyl acrylate mass concentration of 1.6%; the ultrasonic stirring time is 10 min; and the ultrasonic treatment time is 20 min.
7. The method for preparing high-conductivity, high-porosity carbon paper for proton exchange membrane fuel cells according to claim 1, characterized in that: In step S3, the drying time in the oven is one hour and the temperature is 80°C; the vulcanizing bed is hot-pressed in air at a temperature of 150°C and a pressure of 4MPa for 1 hour.
8. The method for preparing high-conductivity, high-porosity carbon paper for proton exchange membrane fuel cells according to claim 1, characterized in that: In step S4, the hot-pressed carbon paper is carbonized in a high-temperature tube furnace at a heating rate of 8-12℃ / min, a sintering temperature of 1000-1200℃, and a holding time of 1 hour. After cooling, carbonized carbon paper is obtained.
9. The method for preparing high-conductivity, high-porosity carbon paper for proton exchange membrane fuel cells according to claim 8, characterized in that: The carbonization process involves a heating rate of 10°C / min, a sintering temperature of 1100°C, and a holding time of 1 hour.
Citation Information
Patent Citations
Gas diffusion layer precursor and preparation method thereof, gas diffusion layer and fuel cell
CN110854402A
Preparation method of high-uniformity double-layer gradient pore carbon paper base paper
CN115262278A